Effects of piglet birth weight and litter size on the preweaning growth performance of pigs on a commercial farm - J R Bergstrom; M L Potter; Steven C Henry; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 2,204 pigs (PIC 327 sired) were used to evaluate the effects of piglet birth weight and litter size on preweaning piglet performance. At a commercial sow farm, all pigs born alive for 22 consecutive days were identified individually at birth with a numbered ear tag. Each sow was assigned a body condition score (BCS; 1 = very thin to 5 = very fat), and the number of total born, live born, and born dead as well as the individual gender, birth weight, and identification of piglets were recorded within 18 h of parturition and before the movement of pigs to equalize litter size. During lactation, all pigs fostered, removed, or found dead were weighed, and the event was recorded. No litters were provided creep feed or supplements during lactation. Pigs were individually weighed and assigned a BCS (1 = emaciated, 2 = thin, or 3 = full-bodied) at weaning over 6 weaning days during a 19-d period, which resulted in a mean weaning age of 25 d. For data analysis, individual birth weight was used to assign pigs to 4 birth weight categories (≤ 2.3 lb, 2.4 to 3.3 lb, 3.4 to 4.3 lb, and ≥ 4.4 lb), and the number of total born in each pig's litter of origin was used to assign pigs to 3 total born categories (≤ 11, 12 to 14, and ≥ 15). As expected, birth weight was greater (P<0.0001) for pigs of heavier birth weight categories. Pigs of heavier birth weight categories were associated (P<0.02) with a decreased number of total and live born. Also, preweaning ADG, weaning weight, weaning BCS, and preweaning mortality were improved (P<0.0001) for pigs of heavier birth weight categories. Birth weight decreased (P<0.04) for pigs of greater total born categories, and an increased sow BCS was associated (P<0.0001) with total born category ≥ 15. As expected, the litter total born, as well as live born and number born dead, increased (P<0.0001) with greater total born categories. Preweaning ADG (0.51, 0.50, and 0.50 lb/d, respectively) and weaning weight (16.3, 15.9, and 15.8 lb, respectively) were modestly improved (P<0.04) for pigs from the smallest total born category compared with the 2 larger categories. These data indicate that low-birth-weight pigs had poorer preweaning growth performance and survivability. Although larger litters resulted in a greater number of low-birth-weight pigs, the number of heavier pigs also increased. In addition to increasing litter size, maximizing reproductive and economic efficiency of swine requires identifying methods to improve birth weight and performance of the lightest pigs born.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Birth weight; Litter size; Swine